2010
DOI: 10.1055/s-0029-1243599
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lipolysis in Adipose Tissues is Associated with Elevation of Systemic Free Fatty Acids and Insulin Resistance in Perilipin Null Mice

Abstract: Elevated plasma levels of free fatty acids (FFAs) are thought to restrict glucose utilization and induce insulin resistance. Plasma FFA concentrations are primarily governed by lipolysis in adipocytes. Perilipin surrounds the lipid droplet in adipocytes and has a dual role in lipolysis regulation. Perilipin null mice studied by two independent laboratories exhibited similar phenotypes of reduced adipose mass and resistance to diet-induced obesity, but have inconsistent metabolic parameters such as plasma level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 37 publications
2
32
1
2
Order By: Relevance
“…As was shown in Fig. 5, plin, the gene of lipid droplet coat protein which may induce lipase LIPE to transport from the cytoplasm into lipid drops [24], was up-regulated, and acsl6, which catalyzes fatty acid activation, was remarkably up-regulated, consistent with the enhanced expression of acsl4 in human NAFLD [25]. The expression level of the genes for elongation elovl3 was remarkably induced in HF groups, while elovl6 was repressed.…”
Section: Discussionsupporting
confidence: 68%
“…As was shown in Fig. 5, plin, the gene of lipid droplet coat protein which may induce lipase LIPE to transport from the cytoplasm into lipid drops [24], was up-regulated, and acsl6, which catalyzes fatty acid activation, was remarkably up-regulated, consistent with the enhanced expression of acsl4 in human NAFLD [25]. The expression level of the genes for elongation elovl3 was remarkably induced in HF groups, while elovl6 was repressed.…”
Section: Discussionsupporting
confidence: 68%
“…However, perilipin-A additionally regulates lipase phosphorylation, thereby enhancing lipolytic reactions. A previous study revealed that perilipin-A-null mice exhibit reduced adipose mass, increased basal lipolysis in adipose tissues, and increased expression and activity of hormone-sensitive and adipose triglyceride lipases (11). Increased lipolytic activity may accelerate the efflux of FFAs from adipose tissues to the bloodstream, and therefore insulin resistance in perilipin-A null mice (11).…”
Section: Discussionmentioning
confidence: 99%
“…Both FFA and glycerol in plasma have been used as rough estimates of lipolysis and mobilization of fatty acid from adipose tissue (40,41). Interestingly, the plasma level of glycerol was elevated in the CXCL1-transfected mice, suggesting an increased rate of lipolysis in these animals (Fig.…”
Section: Discussionmentioning
confidence: 99%